Q‐Rung orthopair fuzzy soft average aggregation operators and their application in multicriteria decision‐making. Issue 4 (17th January 2020) - Hussain, Azmat; Ali, Muhammad Irfan; Mahmood, Tahir; Munir, Muhammad
Abstract: Molodtsov investigated the pioneer notion of soft set ( S f S) which provides a general framework for mathematical problems by affix parameterization tools during the analysis as compared to fuzzy set and q‐rung orthopair fuzzy set (q‐ROFS). The aim of this manuscript is to investigate the notion of q‐rung orthopair fuzzy soft set (q‐ROF S f S), which provide a lay of foundation for those difficulties and complexities which the contemporary theories face during the study of uncertainty. Therefore, our main contribution in this manuscript is to investigate the q‐rung orthopair fuzzy soft weighted averaging, q‐rung orthopair fuzzy soft ordered weighted averaging and q‐rung orthopair fuzzy soft hybrid averaging operators in q‐ROF soft (q‐ROF S f ) environment. Further, the fundamental properties of these aggregation operators are studied. On the base of developed approach an algorithm for multicriteria decision making method is being presented. An application of medical diagnosis problems is solved on the proposed algorithm under the q‐ROF S f environment. Finally, comparison between the developed operators with some existing operators are being presented showing the superiority and efficiency of the developed approach than the existing literature.